2007
DOI: 10.1007/s00216-007-1155-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of a new derivatizing reagent that improves the analysis of amino acids by HPLC with fluorescence detection: application to hydrolyzed rape bee pollen

Abstract: A simple and sensitive method for evaluating the chemical compositions of protein amino acids, including cystine (Cys)(2) and tryptophane (Try) has been developed, based on the use of a sensitive labeling reagent 2-(11H-benzo[alpha]-carbazol-11-yl) ethyl chloroformate (BCEC-Cl) along with fluorescence detection. The chromophore of the 1,2-benzo-3,4-dihydrocarbazole-ethyl chloroformate (BCEOC-Cl) molecule was replaced with the 2-(11H-benzo[alpha]-carbazol-11-yl) ethyl functional group, yielding the sensitive fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 33 publications
3
18
0
Order By: Relevance
“…Bee pollen is flower pollen with nectar and salivary substances of bees and considered as perfect foods due to its nutritional value. It is rich in essential components, including amino acids, proteins, hormones, minerals, and vitamins, and exerts diverse beneficial effect on humans [11,12,13,26,27,28].…”
Section: Resultsmentioning
confidence: 99%
“…Bee pollen is flower pollen with nectar and salivary substances of bees and considered as perfect foods due to its nutritional value. It is rich in essential components, including amino acids, proteins, hormones, minerals, and vitamins, and exerts diverse beneficial effect on humans [11,12,13,26,27,28].…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported the use of (‐)‐1‐(9‐Fluorenyl)ethyl chloroformate (FLEC) reagent for amino acid derivatization. Previously, FLEC has been used for chiral separation of various molecules, including amino acids by HPLC . It has rarely been implemented in CE until now.…”
Section: On‐line Derivatizationmentioning
confidence: 99%
“…With APCI/MS in positive ion detection mode, intense ion current signals for fatty acid derivatives should be attributed to the introduction of the weak basic nitrogen in corresponding TSNPE molecular core structure resulting in high ionization efficiency 16 .…”
Section: Ms Characterization Of the Tsnpe-ffasmentioning
confidence: 99%